Personality, Market Consideration and Student Career Interest in Islamic Financial Institutions: Examining the Moderating Role of Motivation - Nainggolan, Edisah Putra; Rialdy, Novien; Sari, Maya; Hawa, Siti; Winanda, Yola (International Journal of Business Economics (IJBE), 2024)
Purpose – This study examines the effect of personality and market considerations on students' career interest in Islamic Financial Institutions: motivation as a moderating variable in Medan.Methodology – The population in this study were all accounting students at several private universities in Medan City. This study uses purposive sampling with the criteria of Accounting Study Program students in semesters IV and VI. The type of data used in this study is primary data. The data was collected by distributing questionnaires to students. The data analysis technique used is descriptive statistical analysis, and data analysis with statistics used SEM-PLS with the help of Smart PLS software.Findings – The results showed that personality and market considerations significantly affected students' career interest in Islamic Financial Institutions. Furthermore, motivation cannot moderate personality and market considerations significantly affect students' career interest in Islamic financial institutions.Originality/Novelty – The study model includes four variables and uses the notion of moderation by employing SEM-PLS to evaluate each connection in the model.Implications — This study shows that motivation does not moderate the effect of personality and market considerations on student career interest in Islamic financial institutions. Recommendations for future research include analyzing or using motivation variables as independent variables, not moderating variables.